Martire. All’origine dell’essere cristiani - Garribba, Dario (Rassegna di teologia, 2017)
The word “martyr” crosses along all the Christian history, and continues to be able to adapt itself to the historical becoming of the Church. This means that it was a word "discussed” and often “controversal”. The evolution of this path allows us to understand how first Christians elaborated the hermeneutical category of martyrdom as a broader part of the process to define Christian identity.